Mental Health-Related Issues and Quality of Life among Caregivers of Thalassemia Patients (Journal of Social Sciences Review, 2024)
Thalassemia is a lifelong heritable disorder that requires a repetitive blood transfusion procedure. Along with other challenges, caretakers of thalassemic patients must bear the psychosocial burden and stress. This research examined the quality of life of mental health-related issues among caregivers of thalassemic patients. Utilizing a cross-sectional study design, a sample of male and female caregivers /attendants of diagnosed thalassemic patients (N=180) were assessed using the Urdu version of the Quality of Life and The Depression Stress and Anxiety Scales. The results demonstrated a strong relationship between experienced mental health-related issues and quality of life. Further results study also showed substantial gender and family system base differences, showing that male caregivers of thalassemic patients had higher levels of quality of life and fewer mental health-related issues (depression, anxiety, and stress) level than female caregivers of thalassemic patients. Additionally, both gender caregivers of thalassemic patients belonging to the joint family system had a higher level of quality of life with mental health-related issues than the caregivers of thalassemic patients belonging to the nuclear family system.
Keywords: Mental Health; Thalassemia Patients; Blood Transfusion; Psychological Burden; Stress; Depression